Moments together for couples - Rainey, Dennis, 1948-; Rainey, Barbara (Ventura, Calif. : Regal Books, 1995)
Devotions for drawing near to God and one another - On cover.
Includes bibliographical references.
Keywords: Spouses -- Prayers and devotions; Marriage -- Religious aspects -- Christianity; Devotional calendars; Prayers and devotions; Devotional calendars